The effect of rank‐ordering strategy on creative idea selection performance. (2nd May 2021) - Zhu, Yuxi; Ritter, Simone M.; Dijksterhuis, Ap
Abstract: When people have to choose a creative solution from several ideas to tackle a problem, they tend to select mainstream ideas at the expense of creative ideas. In the current research, we examined the effect of rank‐ordering strategy on creative idea selection performance by comparing three different rank‐ordering strategies: choosing (i.e., rank‐ordering ideas by stepwise selecting the most creative idea), elimination (i.e., rank‐ordering ideas by stepwise removing the least creative idea), and paired comparison (i.e., rank‐ordering ideas by making a series of choices from pairs of ideas). In four experiments, participants rank‐ordered 10 ideas in creativity by using one of the three strategies, and the creativity of the most creative idea was compared between the conditions. Moreover, a meta‐analysis was conducted on the data of these four studies. Our findings suggest that rank‐ordering strategy does not influence creative idea selection performance and Bayesian analyses provide evidence supporting the null hypothesis.